Determinants of Financial Distress: Evidence in the Energy Sector - Djazuli, Abid; Yuprizah, Ajeng Bella; Utami, Dinarossi (Universitas muhammadiyah palembang, 2023)
This study aims to determine the effect of Liquidity, Leverage, Activity, and Profitability on the Financial Distress of Energy Sector Companies. The variables studied include Liquidity, Leverage, Activity, and Profitability. The sampling method used in this research is purposive sampling, namely applying certain criteria and eliminating the population according to research needs. The sample used is 47 companies. The data required is secondary data obtained from the Indonesian Stock Exchange through the website www.idx.co.id and related company websites. The data collection method used is the documentation method. The results of the study simultaneously show that the variables of liquidity, leverage, activity, and profitability have an effect on financial distress. Partial research shows that the liquidity variable has an effect on financial distress, the leverage variable has an effect on financial distress, the activity variable has no effect on financial distress, and the profitability variable has an effect on financial distress.